Penggunaan Media Youtube Animasi Dalam Membentuk Profil Pelajar Pancasila Dimensi Berkhebinekaan Global: Studi Deskriptif Kualitatif di SMP Islam Pacet - Kusnadi, Edi; Pitaloka , Yunita (Jayapangus Press, 2024)
Strengthening the profile of Pancasila students is one form of character education for students in Indonesia. With the strengthening of the profile of Pancasila students, it is hoped that Indonesian students will become students who have global competence and behave in accordance with Pancasila values. The purpose of this study was to analyze the use of animated YouTube media to form a profile of Pancasila students with a global diversity dimension. The research conducted was a qualitative descriptive study, data collection using questionnaire techniques, interviews, observations and documentation techniques. The results of the research that has been carried out show the use of animated YouTube media in forming a profile of Pancasila students with a global diversity dimension at SMP Islam Pacet, showing that the use of animated YouTube media has a great influence on strengthening the global diversity dimension in the profile of Pancasila students related to strengthening global diversity characters. The selection of media is very important in the sustainability of strengthening the profile of Pancasila students with a global diversity dimension. The media that can be used is animated YouTube media which is presented in the form of various animated videos. This is in line with the results of the study which resulted in students agreeing that animated YouTube media is a media that is expected to be used in strengthening the Pancasila student profile by students.